2017
DOI: 10.1155/2017/5294290
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and Shear Behaviors of Reinforced Alkali-Activated Slag Concrete Beams

Abstract: The material properties of cement-zero concrete using alkali-activators have been studied extensively as the latest response to reduce the CO 2 exhaust of the cement industry. However, it is also critical to evaluate the behavior of reinforced concrete beams made of alkali-activated slag (AAS) concrete in terms of flexure and shear to promote the applicability of AAS concrete as structural material. Accordingly, nine types of beam specimens with various ratios of tensile steel and stirrup were fabricated and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…The tested beams are shown in Figures 3-6. Sinik and Arsalan, [56] and Lee et al [41] reported similar cracking patterns and failure mechanisms of slender OPC and GPC beams. Deng et al [36] reported that inclined cracking load in slender OPC beams was at about 62-79% of š‘ƒ š‘¢ .…”
Section: Failure Mechanism Of Opc and Gpc Beams Without Stirrupsmentioning
confidence: 82%
See 2 more Smart Citations
“…The tested beams are shown in Figures 3-6. Sinik and Arsalan, [56] and Lee et al [41] reported similar cracking patterns and failure mechanisms of slender OPC and GPC beams. Deng et al [36] reported that inclined cracking load in slender OPC beams was at about 62-79% of š‘ƒ š‘¢ .…”
Section: Failure Mechanism Of Opc and Gpc Beams Without Stirrupsmentioning
confidence: 82%
“…ACI 318-14 [40], ACI 318-19 [42], JSCE-07 [44], and fib-10 [45] underestimated the V c by 71%, 74%, 64% and 79%, respectively. Lee et al [41] investigated GPC beams having a/d ratio 3. ACI 318-14 [40], ACI 318-19 [42], JSCE-07 [44], and fib-10 [45] underestimated the V c by 6-31%, 21-34%, 30-46% and 43-47%, respectively.…”
Section: Gpc Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the stress-strain characteristics of AAM concretes has tended to show that these materials show a higher tensile strength, lower modulus of elasticity, and lower Poisson's ratio than conventional Portland cement concretes, as reported by e.g. [133][134][135] and many others.…”
Section: Microstructure and Mechanical Propertiesmentioning
confidence: 88%
“…The mechanical properties of the concrete as such as bending stress of fibre reinforced concrete which improves with an increase in the percentages of steel fibre. The steel fibres prevent the early deforming of the beams and increase the durability of the structure [9][10][11][12]. The NDT methods for measuring the strength of a structure are not accurate but can help in correlating the values which can help in estimating the strength of the structure and also useful for analyzing the concrete characteristics and its homogeneity.…”
Section: Introductionmentioning
confidence: 99%